Deconstructing the ‘Novel Tourist’ in the ‘New Normal’: An exploration of UK Travel motivations in the aftermath of COVID-19 - Marks, Annie (2022)
Recently, the world has been impacted by the Covid-19 pandemic, which drastically changed consumer lifestyles. In March 2020, the UK population were immediately confined to their homes, whereby mundane activities became frowned upon and even illegal. Consequently, all international travel halted which had detrimental effects on the tourism industry. This paper aims to address the gap in empirical research concerning consumer motivations in the aftermath of Covid-19. This research aims to deconstruct the ‘novel tourist’ in terms of their underlying motivations to travel abroad post-Covid-19. It also aims to examine the role of Destination Trust in consumers’ decision-making. Literature on tourist motivations has focused on utilising the Theory of Planned Behaviour (TPB) to understand why tourists travel; however, there are limited studies replicating research focused on the presence of Covid-19. By taking a novel approach to evaluating motivations, this research introduces the concept of Goal Framing Theory (GFT) into the context of Covid-19 and tourism by employing a quantitative study to test causal relationships in a sample of 116 people. Most saliently, the research findings deconstruct the goals behind consumers’ motivations to travel abroad post-pandemic, finding that three Goal Frames emerged: Gain-Hedonic, Gain-Norm and Social Norms. When testing the Goal Frames’ relationship with intentions, only Social Norms were found to be a significant predictor. This study took this further, by looking at the mediating effect of Destination Trust in the model, concluding that trust mediated the relationship between both Social Norms and Gain-Hedonic Goal Frames with intentions. Moreover, the findings also show that intentions moderately predicted behaviour. Lastly, this study proved the assumption that consumer trust has depleted from before the pandemic, adding to the importance of the study. The findings provide support for the use of GFT in the context of tourism and Covid-19, whilst also enhancing the model to include the evaluation of sub-goals, having theoretical contributions. Furthermore, the findings offer guidance for tourism marketers to focus their campaigns on certain consumer goals. Overall, it concludes that Goal Frames have changed because of the Covid-19 pandemic.